Why the effective price for money exceeds the policy rate in the ECB tenders? - Tuomas Välimäki (European Central Bank (ECB), 2008)
The tender spread, i.e. the difference between the effective price for money in the ECB's main refinancing operations and the prevailing policy rate, is one of the main determinants behind the evolution of the EONIA with respect to the ECB's operational target. This study assesses the reasons for which the average tender spread did not reduce after the banks' demand for liquidity was isolated from their interest rate expectations in March 2004. The paper offers two potential explanations for the unexpected behavior. First, following the increased precision in the ECB's liquidity provision after the end-of- period fine tuning operations were added to the regularly applied tools, even a small bias in the liquidity supply could have resulted in a strictly positive tender spread. Second, banks' uncertainty over their individual allotments in the tender operations may have led to a strictly positive tender spread. Furthermore, the significant growth in the refinancing volumes may have intensified the allotment uncertainty.
Keywords: D44; E58; 330; EONIA; liquidity; main refinancing operations; tenders; Zentralbank; Geldpolitik; Zinsstruktur; Tagesgeldmarkt; Auktion; EU-Staaten